2013
DOI: 10.1371/journal.pone.0053711
|View full text |Cite
|
Sign up to set email alerts
|

Laser Capture Microdissected Mucosa versus Whole Tissue Specimens for Assessment of Radiation-Induced Dynamic Molecular and Pathway Changes in the Small Intestine

Abstract: BackgroundThe intestinal mucosa is the compartment that sustains the most severe injury in response to radiation and is therefore of primary interest. The use of whole gut extracts for analysis of gene expression may confound important changes in the mucosa. On the other hand, laser capture microdissection (LCM) is hampered by the unstable nature of RNA and by a more complicated collection process. This study assessed, in parallel samples from a validated radiation model, the indications for use of LCM for int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This results in the processing of p100 and is negatively regulated by molecules such as cIAP1, A20, and TRAF3 (Figure 3). Although XEDAR has not been investigated in IBD, it has been shown to be greatly upregulated in the gastrointestinal mucosa of nonhuman primates and mice after radiation exposure (71, 72). This may have functional implications in IBD, where mucosal epithelial cell turnover and barrier integrity are critical events in the inflammatory process.…”
Section: Working Like a Well-oiled Machine: Positive Regulation Of Nomentioning
confidence: 99%
“…This results in the processing of p100 and is negatively regulated by molecules such as cIAP1, A20, and TRAF3 (Figure 3). Although XEDAR has not been investigated in IBD, it has been shown to be greatly upregulated in the gastrointestinal mucosa of nonhuman primates and mice after radiation exposure (71, 72). This may have functional implications in IBD, where mucosal epithelial cell turnover and barrier integrity are critical events in the inflammatory process.…”
Section: Working Like a Well-oiled Machine: Positive Regulation Of Nomentioning
confidence: 99%
“…This is consistent with the results from Zheng et al, who, when studying irradiated mice, found activated pathways mediating repair, apoptosis, coagulation and cell cycle control. 23 Interestingly, when looking at negative and positive dose-correlated probes separately, the positively correlated pathways (demethylated) had a lower FDR, suggesting that demethylation of genes is more prominent after irradiation. We found that irradiation resulted in demethylation of pathways either involved in the immune system response or in cell proliferation and survival.…”
Section: Altered Pathways As a Results Of Irradiationmentioning
confidence: 99%
“…Within the dose‐dependent gene list, a significant change in methylation pattern for pathways associated with cellular immune response, cell cycle regulation and apoptosis was found, representing mechanisms known to be important in radiation response. This is consistent with the results from Zheng et al ., who, when studying irradiated mice, found activated pathways mediating repair, apoptosis, coagulation and cell cycle control . Interestingly, when looking at negative and positive dose‐correlated probes separately, the positively correlated pathways (demethylated) had a lower FDR, suggesting that demethylation of genes is more prominent after irradiation.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, assessment of tissue layer profiles is crucial to correlate identified molecular patterns with clinical outcomes. In fact, laser-capture microdissection (LCM) coupled with gene expression analysis [4][5][6][7][8][9][10][11][12][13] has therefore been established. LCM enables separation of tissue sub-regions providing histologically pure enriched cell populations.…”
Section: Introductionmentioning
confidence: 99%